Development of microbial granules under alternating aerobic-anaerobic conditions for carbon and nitrogen removal - Qin, Lei (2008)
Aerobic granulation is a novel environmental biotechnology recently developed for wastewater treatment. Nearly all research on aerobic granulation has been conducted in sequencing batch reactors (SBR); however, the effect of one of the most important operating parameters in SBR, i.e. settling time, is still unknown on the formation of aerobic granules. Thus, the first part of the present research investigated the effect of settling time on the development of aerobic granules. For this purpose, four SBRs were operated at different settling times of 5 to 20 minutes. Results showed that aerobic granules were successfully cultivated and became dominant only in the SBR operated at the shortest settling time of 5 minutes, while a mixture of aerobic granules and suspended sludge was observed in the reactors run at settling times of 20, 15 and 10 minutes, respectively.